2015
DOI: 10.1007/s00508-015-0887-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with motor performance among overweight and nonoverweight Tyrolean primary school children

Abstract: Regarding modifiable factors, motor performance among overweight and nonoverweight children is strongly associated with a higher number of weekly lessons in physical education. Therefore, daily lessons in physical education are strongly recommended to improve motor performance especially among overweight primary school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
3
21
1
Order By: Relevance
“…The proportion of children with migration background in this longitudinal study (26%) is well in accordance with cross-sectional studies by Greier and Riechelmann 17 among Tyrolean preschool children (25%), and by Ruedl et al 14 among Tyrolean primary school children (26%) and well comparable with a recent cross-sectional study by Kaiser-Jovy et al 5 among Tyrolean secondary school children (22%).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The proportion of children with migration background in this longitudinal study (26%) is well in accordance with cross-sectional studies by Greier and Riechelmann 17 among Tyrolean preschool children (25%), and by Ruedl et al 14 among Tyrolean primary school children (26%) and well comparable with a recent cross-sectional study by Kaiser-Jovy et al 5 among Tyrolean secondary school children (22%).…”
Section: Discussionsupporting
confidence: 92%
“…Our results reveal that it seems hardly possible to catch up this baseline deficit in physical fitness in the school setting without additional physical activity outside the school, for example in organized sports. In our earlier work among a cohort of primary school children, we found that active participation in a sports club was a significant predictor for a higher physical fitness in non‐overweight and overweight children. Also Golle et al showed in a 4‐year longitudinal study a significantly better motor performance development for endurance and lower‐extremity strength for children continuously participating in sports clubs compared to their non‐participating peers.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Jump and reach performance increased by 12% from 1972 to 2015 (F=7.58; total df: 210; p=0.007) (Figure 1) Anderssen, Andersen, Steene-Johannessen, Ekelund, Hansen & Kolle, 2018;Dollman, Norton & Norton, 2005;Sigmundova, El Ansri, Sigmnund & Frömel, 2011). Along with these behavioral changes there has also been an increase in the prevalence of overweight and obesity (Ahluwalia et al, 2015;Jackson-Leach & Lobstein, 2006;Kelly, Yang, Chen, Reynolds & He, 2008;Moß, Wabitsch, Kromeyer-Hauschild, Reinehr & Kurth, 2007;Reilly, Methven, McDowell, Hacking, Alexander, Stewart & Kelnar, 2003;Pigeot & Walter, 2016;Wang & Lobstein, 2006), which is inversely related with endurance capacity (Graf et al, 2004;Greier, Riechelmann & Burtscher, 2014;Lakoski, Barlow, Farrell, Berry, Morrow & Haskell, 2011;Ruedl, Greier, Kirschner & Kopp, 2016;Starker et al 2007). This is of particular concern, as low cardiorespiratory fitness and excess body weight are risk factors for various chronic diseases (Dietz, 1998;Hurtig-Wennlöf, Ruiz, Harro, & Sjöström, 2007;Stabelini Neto et al 2011).…”
Section: Motor Competence Across Timementioning
confidence: 99%